An approach to death as an adverse event following immunization. Issue 2 (4th January 2016) - Gold, Michael S.; Balakrishnan, Madhava Ram; Amarasinghe, Ananda; MacDonald, Noni E.
Abstract: Co-incidental death occurring proximate to vaccination may be reported as an adverse event following immunization. Such events are particularly concerning because they may raise community and health provider concerns about the safety of the specific vaccine and often the immunization programme in general. Coincidental events need to be differentiated from vaccine reactions, such as anaphylaxis, which may very rarely result in death. In 2013, the World Health Organization (WHO) released an updated manual for the Causality Assessment of an AEFI. The purpose of this review is to apply the WHO causality methodology to death when this is reported as an AEFI. The causality assessment scheme recommends a four step process to enable classification of the AEFI and to differentiate events which are causally consistent from those that are inconsistent with immunization. However, for some events causality maybe indeterminate. Consistent causal reactions that may result in death are very rare and maybe related to the vaccine product (e.g. anaphylaxis, viscerotrophic disease), vaccine quality defect (e.g. an incompletely attenuated live vaccine agent) or an immunization error (e.g. vaccine vial contamination). Events that are inconsistent with immunizations are due to co-incidental conditions that may account for infant and childhood mortality. In countries with a high infant mortality rate the coincidental occurrence of death and immunization may occur not infrequently and a robust mechanism to obtain information from autopsy and perform an AEFI investigation and causality assessment is essential. Communication with the community and all stakeholders to maintain confidence in the immunization programme is critical.